Принцип роботи пристроїв з енергонезалежною електричною пам’яттю - Бураковська, М. С. (ХНУРЕ, 2024)
This scientific work is devoted to studying the principle of devices with non volatile memory, which is an important aspect of modern electronics.Various technologies, such as memory based on electric charges, magnetoresistive memory, and phase change memory, are considered in terms of their operation and applications principles. The evolution of creating each type of memory is described. The work reveals advantages such as energy efficiency and high reliability, as well as analyzes the technical and economic challenges associated with the production and implementation of these technologies.
Keywords: електрична пам’ять; енергонезалежна пам’ять